Effectiveness of different compression-to-ventilation methods for cardiopulmonary resuscitation: A systematic review. (September 2017) - Ashoor, Huda M.; Lillie, Erin; Zarin, Wasifa; Pham, Ba'; Khan, Paul A.; Nincic, Vera; Yazdi, Fatemeh; Ghassemi, Marco; Ivory, John; Cardoso, Roberta; Perkins, Gavin D.; de Caen, Allan R.; et al.
Abstract: Aim: To compare the effectiveness of different compression-to-ventilation methods during cardiopulmonary resuscitation (CPR) in patients with cardiac arrest. Methods: We searched MEDLINE and Cochrane Central Register of Controlled Trials from inception until January 2016. We included experimental, quasi-experimental, and observational studies that compared different chest compression-to-ventilation ratios during CPR for all patients and assessed at least one of the following outcomes: favourable neurological outcomes, survival, return of spontaneous circulation (ROSC), and quality of life. Two reviewers independently screened literature search results, abstracted data, and appraised the risk of bias. Random-effects meta-analyses were conducted separately for randomised and non-randomised studies, as well as study characteristics, such as CPR provider. Results: After screening 5703 titles and abstracts and 229 full-text articles, we included 41 studies, of which 13 were companion reports. For adults receiving bystander or dispatcher-instructed CPR, no significant differences were observed across all comparisons and outcomes. Significantly less adults receiving bystander-initiated or plus dispatcher-instructed compression-only CPR experienced favourable neurological outcomes, survival, and ROSC compared to CPR 30:2 (compression-to-ventilation) in un-adjusted analyses in a large cohort study. Evidence from emergency medical service (EMS) CPR providers showed significantly more adults receiving CPR 30:2 experiencing improved favourable neurological outcomes and survival versus those receiving CPR 15:2. Significantly more children receiving CPR 15:2 or 30:2 experienced favourable neurological outcomes, survival, and greater ROSC compared to compression-only CPR. However, for children <1 years of age, no significant differences were observed between CPR 15:2 or 30:2 and compression-only CPR. Conclusions: Our results demonstrated that for adults, CPR 30:2 is associated with better survival and favourable neurological outcomes when compared to CPR 15:2. For children, more patients receiving CPR with either 15:2 or 30:2 compression-to ventilation ratio experienced favourable neurological function, survival, and ROSC when compared to CO-CPR for children of all ages, but for children <1 years of age, no statistically significant differences were observed.